Music students' psychological profiles: unveiling three coping clusters using schema mode inventory - Wenhart, Teresa; Hildebrandt, Horst (Frontiers in Psychology, 2026)
Background and aimProfessional musicians face unique psychological demands leading to elevated rates of mental health problems, including depression, anxiety, and performance anxiety, as well as stress-related disorders. These difficulties are associated with perfectionism, adverse experiences, and maladaptive coping strategies. While schema modes—recurring emotion, cognitive, and behavioral patterns triggered by early maladaptive schemas—are well-studied in clinical populations, their role in musicians remains unexplored. This study explores schema-mode presence in music students to evaluate their utility for understanding psychological vulnerability and coping.MethodsIn total, 46 music students from Zurich University of the Arts and Basel Music Academy completed an online survey assessing schema modes (short Schema Mode Inventory), musician-specific coping (HIL scale), and self-talk and complaints related to music-making via open-ended questions. Analysis included comparisons of effect sizes with normative summary data from healthy controls and clinical patients, inter-correlations between schema-modes and coping, cluster analysis identifying psychological profiles, and qualitative content analysis.ResultsMusic students scored significantly higher on maladaptive schema-modes vs. non-clinical controls, indicating greater emotional coping difficulties and reduced adaptive resources. Coping capacity correlated negatively with maladaptive modes and positively with the Healthy Adult mode. Scores overlapped with those of Axis I patients but differed from Axis II patients, suggesting intermediate clinical characteristics. Cluster analysis revealed three distinct profiles: “Balanced Musicians” (resilient cluster with high Healthy Adult and Happy Child modes and effective coping), “Vulnerable Musicians” (high-risk cluster with intense emotional child modes and frequent maladaptive parent/coping modes), and “Compensating Musicians” (at-risk cluster with intermediate scores and overcompensating strategies combining functional and maladaptive modes).ConclusionSchema modes appear central to musicians' mental health and coping, highlighting psychological profile heterogeneity among music students. Schema-focused interventions targeting maladaptive modes may enhance resilience and mental health in this population. This approach offers a promising clinical framework for supporting musicians' wellbeing.